An Analysis Of Code Switching Employed By The Characters Anna And Kate In The Film Melodylan - Maulana, Bahtiar; Larasati, Agnes; Shofiana Jamilah, Ana; Zulaicha, Putri (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2023)
Language plays a vital role in facilitating communication within diverse communities, enabling speakers to enhance their understanding and articulate insights, perspectives, and ideas effectively. In multilingual societies, individuals frequently alternate between languages to meet communicative demands—a phenomenon known as code switching. This study investigates: (1) the types of code switching utilized by the characters Anna and Kate in the film Melodylan, and (2) the underlying factors motivating such language alternation. Employing a descriptive qualitative method, this research examines the dialogue between the two characters. The findings reveal three types of code switching: inter-sentential, intra-sentential, and tag switching. Furthermore, six key motivations for code switching were identified: addressing specific topics, expressing empathy, using interjections, repetition for clarification, clarifying messages for the listener, and asserting group identity.